1992
DOI: 10.3406/ecmed.1992.1708
|View full text |Cite
|
Sign up to set email alerts
|

Typification de syntaxa décrits en région méditerranéenne orientale

Abstract: En conformité avec les règles du code de nomenclature phytosociologique, les auteurs valident par la désignation de lectotypes, les unités supérieures et les associations non valablement décrites, qu’ils avaient publiées dans divers travaux relatifs à la végétation de la Méditerranée Orientale. Un certain nombre de modifications mineures sont apportées dans la désignation des syntaxa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 0 publications
0
41
0
Order By: Relevance
“…Concerning the syntaxonomical ar-rangement, the association was included by BARBERO & QUEZEL (1976) in a special alliance, named Pino-Chamaecytision, belonging to the Quercetalia pubescentis. Together with the Seslerio robustae-Pinetum pallasianae, it was included in the Pino-Chamaecytision also the association Staehelino uniflosculosae-Pinetum pallasianae, successively chosen by QUEZEL et al (1992) as its lectotype. Indeed, the last association designates a forest vegetation rich in nemoral species of Quercetalia pubescentis, while Seslerio robustae-Pinetum pallasianae, as already affirmed, is an open pine-wood primarily occurring on soils not much evolved and rich in skeleton, where the nemoral species are sporadic.…”
Section: Ass F'terocephalo Perennisjuniperetum Foetidissimae Georgiamentioning
confidence: 99%
“…Concerning the syntaxonomical ar-rangement, the association was included by BARBERO & QUEZEL (1976) in a special alliance, named Pino-Chamaecytision, belonging to the Quercetalia pubescentis. Together with the Seslerio robustae-Pinetum pallasianae, it was included in the Pino-Chamaecytision also the association Staehelino uniflosculosae-Pinetum pallasianae, successively chosen by QUEZEL et al (1992) as its lectotype. Indeed, the last association designates a forest vegetation rich in nemoral species of Quercetalia pubescentis, while Seslerio robustae-Pinetum pallasianae, as already affirmed, is an open pine-wood primarily occurring on soils not much evolved and rich in skeleton, where the nemoral species are sporadic.…”
Section: Ass F'terocephalo Perennisjuniperetum Foetidissimae Georgiamentioning
confidence: 99%
“…Özen (2010) said that this forest was the same as the Fraxinus angustifolia-dominated forests in Samsun Province studied by Kutbay et al (1998). Kutbay et al (1998) called the community Pterocaryo pterocarpae -Fraxinetum angustifoliae, indicating that the floristic composition of the community is highly similar (49.46%) to that reported by Quézel et al (1992). Although Özen (2010) called the community Alno glutinosae -Fraxinetum angustifoliae, he did not make any syntaxonomic identification about the community.…”
Section: Euro-siberianmentioning
confidence: 99%
“…Cluster 6 was identified by Kutbay et al (1998) as the same community as the communities described by Quézel et al (1980) in Samsun Province and Aydoğdu (1988) in Sakarya Province. Kutbay et al (1998) called the community Pterocaryo pterocarpae -Fraxinetum angustifoliae, whereas Quézel et al (1992) nominated the community as Pterocaryo fraxinifoliae -Alnetum barbatae. On the other hand, our classification analysis showed that this forest was different from the communities studied by Quézel et al (1980) and Aydoğdu (1988).…”
Section: Euro-siberianmentioning
confidence: 99%
See 1 more Smart Citation
“…1934(QuCzel, 1973Qutzel, Barber0 & b a n , 1992). While the Onosmetalia fitescentis order is frequent on limestone rocks below 1500 m elevation in the Mediterranean Region, the Asplenietea rupestria class is represented in all rocky vegetation in the Northern Hemisphere (QuCze1, 1973;QuCzel et al, 1992).…”
Section: Phenologymentioning
confidence: 99%